2017
DOI: 10.1038/s41598-017-05107-4
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Staphylococcus aureus from Escherichia coli mastitis: S. aureus triggers unbalanced immune-dampening and host cell invasion immediately after udder infection

Abstract: The etiology determines quality and extent of the immune response after udder infection (mastitis). Infections with Gram negative bacteria (e.g. Escherichia coli) will quickly elicit strong inflammation of the udder, fully activate its immune defence via pathogen receptor driven activation of IκB/NF-κB signaling. This often eradicates the pathogen. In contrast, Gram-positive bacteria (e.g. Staphylococcus aureus) will slowly elicit a much weaker inflammation and immune response, frequently resulting in chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 69 publications
5
88
0
Order By: Relevance
“…During inflammation, predominant types of SC are neutrophils followed by macrophages and lymphocytes, which enters the mammary gland from blood 38 . MSCs have been shown to induce immunomodulatory control on neutrophils, macrophages and lymphocytes by secretion of several factors including cytokines IL-6, IL-10, PGE2 and IDO [39][40][41][42] . We previously reported that bovine fetal AT-MSCs responds to inflammatory stimulation by up-regulation of IDO and IL-6 9 .…”
Section: Days Post-infectionmentioning
confidence: 99%
“…During inflammation, predominant types of SC are neutrophils followed by macrophages and lymphocytes, which enters the mammary gland from blood 38 . MSCs have been shown to induce immunomodulatory control on neutrophils, macrophages and lymphocytes by secretion of several factors including cytokines IL-6, IL-10, PGE2 and IDO [39][40][41][42] . We previously reported that bovine fetal AT-MSCs responds to inflammatory stimulation by up-regulation of IDO and IL-6 9 .…”
Section: Days Post-infectionmentioning
confidence: 99%
“…In the course of long phylogeny in mammals, clear mechanisms of interaction between microorganisms and the organism of animals and humans were formed, and the immune protection system was evolved, and immunity was formed (Ceniti et al, 2017;Ding et al, 2019). In the modern sense of immunity means the ability of the body to protect itself from genetically extraneous (as well as other pathogenic factors), aimed at maintaining biological homeostasis (Kurjogi & Kaliwal, 2014;Günther et al, 2017;. The stability of the internal environment of an organism depends on its reactivity and ability to counteract the harmful environmental factors (Zhelavskyi, 2010;Zhelavskyi, 2014;Zhelavskyi, 2015;Zhelavskyi, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies have also proven that lactoferrin stimulates the activity of lactoperoxidase. The susceptibility to E. coli and Staphylococcus aureus was shown, that microbial strains of Streptococcus agalactiae, Streptococcus dysgalactiae and Streptococcus uberis, which have lactoferrin binding proteins on their surface, reduce the bactericidal effect of lactoferrin (Oudessa and Almeida, 2011;Günther et al, 2017). Also the data on immunomodulatory and neutralizing properties of lactoferrin were published.…”
Section: Resultsmentioning
confidence: 99%